Penerapan Personal Information Management (PIM) Pada Mahasiswa Tingkat Akhir - Ulfa Rizkina; Ruslan; Asnawi, Asnawi (Indonesian Journal of Library and Information Science, 2023)
Personal Information Management (PIM) is a method or practice that can assist in managing personal information stored in storage media, making it easier to find the information owned. One of them is the final year students of the Library Science Study Program who are expected to be able to manage personal information effectively, both past and current information. This phenomenon makes its own interest to find out the description of Personal Information Management developed by UIN Ar-Raniry students during the thesis work period. The method used in this research is descriptive quantitative method. The subject of this research is the 2018 class of Library Science Study Program students consisting of 57 respondents. The data collection technique used is using questionnaire distribution and the data analysis method used is using the mean formula. The results of the research on the finding indicator show that 64.9% of students explore thesis material from various sources, then 47.4% of students connect keywords related to the search for thesis material, and 43.9% of students conduct direct searches for thesis material using specific keywords and reading material flashes. Furthermore, keeping and organizing information shows 54.4% of students agree to select the usefulness of the information before it is actually stored and 56.1% of students store thesis material in folders that are easy to remember. For Meta-level, information maintenance 64.9% of students will back-up and update information and 61.4% of students agree to always manage information in and out of storage media in order to save storage space.